Significados Que, Frente a La Reparación Integral, Construyen Víctimas De Desplazamiento Forzado En Colombia (2019)
This research belongs to a qualitative epistemology based on the methodology of symbolic interactionism, in which was analysed the significance of forced displacement on a group of 5 people who have fallen victim to it, people who have direct experience in the Colombian armed conflict and who are currently in the full reparation process carried out by the Colombian government. The analysis focussed on five main categories set out in Law 1448 of 2011 on full reparation and one emerging category: reparation, human rights, prevention of anything similar happening again, restitution of lands, justice and truth, and, ultimately, the future. Having interviewed the participants, the conclusion is that the important parts of the compensation for them are both individual and shared goals.